Moral Fire : Musical Portraits from America's Fin de Siècle. - Horowitz, Joseph (University of California Press, 2012)
Joseph Horowitz writes in Moral Fire: "If the Met's screaming Wagnerites standing on chairs (in the 1890s) are unthinkable today, it is partly because we mistrust high feeling. Our children avidly specialize in vicarious forms of electronic interpersonal diversion. Our laptops and televisions ensnare us in a surrogate world that shuns all but facile passions; only Jon Stewart and Bill Maher share moments of moral outrage disguised as comedy." Arguing that the past can prove instructive and inspirational, Horowitz revisits four astonishing personalities--Henry Higginson, Laura Langford, Henry.